Transformações na indústria do fitness e o trabalho de professores de educação física - Silva, Nathália Costa Melo e (2023)
Academic master's dissertation developed by the Graduate Program of the Faculty of Physical Education and Dance at the Federal University of Goiás. It aimed to analyze the fitness industry transformations and its chains in the organization of the work of Physical Education teachers at this segment over the last three decades. For data collection, a field research on focus groups with 4 to 6 participants each was carried out, this groups were formed by Physical Education teachers who work in the fitness industry. A documentary analysis of materials found on websites about the current characteristics of this market segment was carried out as well. It can be comprehended that in the last decades there was a significantly increase of liberal work within fitness, embodied in Personal Trainer’s image. On the other hand, there is a decrease of salaried teachers in the fitness center as a result of the new gyms’ models which emerged from the low-cost company modal. Other characteristics like collective gymnastics, which had great strength in gyms in the 2000s, have undergone major transformations recently. And information and communication technologies have increasingly penetrated the fitness industry and caused changes in the work of teachers. The transformations that have occurred in the fitness segment in recent decades are anchored by the economic and social transformations of these periods.